2022
DOI: 10.1186/s12979-022-00284-x
|View full text |Cite
|
Sign up to set email alerts
|

Markers of systemic inflammation are positively associated with influenza vaccine antibody responses with a possible role for ILT2(+)CD57(+) NK-cells

Abstract: Background With increasing age, overall health declines while systemic levels of inflammatory mediators tend to increase. Although the underlying mechanisms are poorly understood, there is a wealth of data suggesting that this so-called “inflammaging” contributes to the risk of adverse outcomes in older adults. We sought to determine whether markers of systemic inflammation were associated with antibody responses to the seasonal influenza vaccine. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 71 publications
1
10
0
Order By: Relevance
“…While novel, these findings also represent a limitation of our study as we were unable to determine the mechanistic basis for this relationship or elucidate the phenotype of these cell types beyond their parental lineage; in fact, there may even be a relevant role for the aging-and CMV-related CD56-negative NK-cell subset, which we were unable to identify (Müller-Durovic et al, 2019). An exploratory analysis using immunophenotyping data published as part of a previous study (Picard et al, 2022) showed that the frequency of GZK+ NK-cells most strongly correlated with the frequency of CD56 dim NKG2A + NKG2C + NK-cells (d = .41; data not shown), which suggest a developmentally intermediate (i.e., from CD56 bright GZK + to CD56 dim GZK − NK-cells) or even tissue-resident phenotype (Yang et al, 2019;Melsen et al, 2022). Interestingly, we found that two markers of lymph node NK-cells, NKp46 and NKp30 (Eissens et al, 2012;Dogra et al, 2020), were also inversely correlated with A/H1N1 antibody responses in that previous study (Picard et al, 2022).…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…While novel, these findings also represent a limitation of our study as we were unable to determine the mechanistic basis for this relationship or elucidate the phenotype of these cell types beyond their parental lineage; in fact, there may even be a relevant role for the aging-and CMV-related CD56-negative NK-cell subset, which we were unable to identify (Müller-Durovic et al, 2019). An exploratory analysis using immunophenotyping data published as part of a previous study (Picard et al, 2022) showed that the frequency of GZK+ NK-cells most strongly correlated with the frequency of CD56 dim NKG2A + NKG2C + NK-cells (d = .41; data not shown), which suggest a developmentally intermediate (i.e., from CD56 bright GZK + to CD56 dim GZK − NK-cells) or even tissue-resident phenotype (Yang et al, 2019;Melsen et al, 2022). Interestingly, we found that two markers of lymph node NK-cells, NKp46 and NKp30 (Eissens et al, 2012;Dogra et al, 2020), were also inversely correlated with A/H1N1 antibody responses in that previous study (Picard et al, 2022).…”
Section: Discussionmentioning
confidence: 92%
“…Although NK-and CD8 + T-cells are most often associated with the cytolytic response to respiratory infection, previous studies suggest that they are also important for vaccine-induced antibody responses to antigens from influenza (Herrero-Fernández et al, 2019;Picard et al, 2022) and other pathogens (Kalia et al, 2021). Given this, we sought to determine whether cell-specific granzyme expression was associated with hemagglutination inhibition (HAI) antibody titres prior to and following seasonal high-dose vaccination in our older adult participants.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is prudent to consider here that the significance of compromised functions of the immune system during aging in augmenting organismal risk of infections and delayed immune response appears contentious. On one hand, there is mounting evidence that age-dependent functional and phenotypic changes in immune cells can contribute to reduced vaccine response and increased risk of infections during aging (He et al 2021 ; Loyer et al 2022 ; Sabbatinelli et al 2022 ; Simmons et al 2022 ); on the other hand, there are also reports indicating that aspects of immunosenescence, such as inflamm-aging, could be positively corelated with increased vaccine immunogenicity in older adults (Picard et al 2022 ). These conflicting observations corroborate the recent efforts of Pawelec et al that highlighted the limitations and lacunae of the prevailing one-dimensional view of immunosenescence (Pawelec et al 2020 ).…”
Section: Introductionmentioning
confidence: 99%